Faktor-Faktor yang Mendorong Likuidasi Anak Perusahaan serta Pengaruhnya terhadap Reputasi Perusahaan di Sektor Perbankan - Desanti Al Fadilah; Amanda Rizky Arie Fadhilah; Salma Septiana; Masrukhan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The liquidation of a subsidiary in the banking sector is a strategic step with a significant impact on the financial performance, reputation, and sustainability of the parent company. This study aims to analyze the factors that drive liquidation, both internal such as financial performance, mismanagement, and legal compliance, as well as external such as market changes, natural disasters, and globalization pressures. Data were collected through academic literature review using qualitative approaches and data triangulation to improve the reliability of the results. The results of the study show that poor liquidity management, both due to internal and external factors, is the main cause of liquidation. The impact on the reputation of the parent company is dualistic: on the one hand it increases operational efficiency, but on the other hand it risks creating negative perceptions, such as management failures or employee losses. Therefore, companies must strengthen financial management, utilize technology to monitor cash flow in real-time, and develop flexible risk policies. Transparent communication with stakeholders is also important to minimize reputational impact. This study shows that effective liquidity management supports operational efficiency and increases public confidence, customers, and regulators, relevant for both Islamic and conventional banking in dealing with market dynamics.